2017
DOI: 10.29252/iueam.5.20.83
|View full text |Cite
|
Sign up to set email alerts
|

Determining Scenario-Based Strategies in the Land and Housing Organization of Mashhad City

Abstract: The aim of this research is to codify scenario-based strategies in the Land and Housing Organization that has been done with drawing pictures of the future. In the present study, we used Schwartz and simultaneous methods in order to determine the strategies. The present study has been done in the year 2015 within the time horizon of 10 years. The statistical population included all senior municipal managers and experts in the Land and Housing Organization of Mashhad city (27 persons) which 15 persons selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…16 In the same context, Ramezani in the Charter of Professional Ethics has indicated that trust in God and spiritual values can facilitate ethical management in an organization. 30 In general, he referred to compassion, patience, observance of justice, secretiveness, trustworthiness, and work conscience. 19 Rezapour Nasrabad 15 pointed to patience and secretiveness as the major characteristics of managers and regarded them as the spiritual capacity to accept science, power, as well as all perceptions and feelings.…”
Section: Professional Ethicsmentioning
confidence: 99%
“…16 In the same context, Ramezani in the Charter of Professional Ethics has indicated that trust in God and spiritual values can facilitate ethical management in an organization. 30 In general, he referred to compassion, patience, observance of justice, secretiveness, trustworthiness, and work conscience. 19 Rezapour Nasrabad 15 pointed to patience and secretiveness as the major characteristics of managers and regarded them as the spiritual capacity to accept science, power, as well as all perceptions and feelings.…”
Section: Professional Ethicsmentioning
confidence: 99%